Perlindungan Hukum Pemegang Saham Minoritas terhadap Penyalahgunaan Kekuasaan Pemegang Saham Mayoritas di Indonesia dan Singapura - Takke, Shareen Virgita Septalia (Media Hukum Indonesia (MHI), 2026)
The imbalance of power between majority and minority shareholders in Indonesian private companies creates significant opportunities for majority shareholders to exercise their rights in a manner detrimental to minority interests. Various jurisdictions have addressed this issue through substantive mechanisms such as the oppression remedy, exemplified by Singapore’s Section 216 of the Companies Act, which employs a standard of commercial fairness to determine whether majority conduct though formally compliant constitutes oppressive or unfairly prejudicial treatment. However, Indonesia has not adopted a similar doctrine; minority protection remains procedural under Law No. 40/2007, which does not directly regulate majority oppression. This study employs doctrinal legal research using conceptual, comparative, and statutory approaches to examine forms of majority shareholder abuse and evaluate the adequacy of existing protections. The findings show that Indonesia’s mechanisms remain limited to correcting formal violations, whereas Singapore provides substantive and flexible remedies, including buy-out orders, through broad judicial discretion. The study concludes that Indonesia must strengthen its substantive legal framework to offer more effective protection for minority shareholders.